TRANSFORMASI TRANSAKSI KEUANGAN ISLAM: MENDORONG KEPATUHAN SYARIAH MELALUI TEKNOLOGI BLOCKCHAIN - Ayu Yuningsih; Huril A'ini (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2026)
Digital transformation has significantly reshaped the global financial system, including the Islamic finance industry, which is required to maintain strict compliance with Sharia principles. This study aims to analyze the role of blockchain technology in transforming Islamic financial transactions to enhance Sharia compliance, as well as to identify the key challenges in its implementation. This research employs a library research method using a content analysis approach on relevant academic literature published between 2018 and 2025. The findings reveal that blockchain holds significant potential to improve transparency, accountability, and transaction efficiency through its distributed, immutable, and real-time verifiable ledger system. Furthermore, the implementation of smart contracts enables the automation of Sharia-based contracts, reducing moral hazard and ensuring consistent adherence to Islamic principles. However, the adoption of blockchain in Islamic finance still faces several challenges, including regulatory uncertainty, limited human capital, inadequate technological infrastructure, and difficulties in integrating with existing financial systems. This study concludes that the successful implementation of blockchain in Islamic finance requires a comprehensive and collaborative approach involving regulators, practitioners, academics, and Sharia scholars to ensure alignment between technological innovation and Islamic values.